Amyloid‐β analysis from brain cells using microfluidics and mass spectrometry. (December 2021) - Villarreal, Jorvani Cruz; Egatz‐Gomez, Ana; Liu, Jiawei; Ros, Robert; Noutsios, George T.; Sandrin, Todd R.; Coleman, Paul D.; Ros, Alexandra
Abstract: Background: Soluble amyloid β (Aβ) oligomers are identified as the main neurotoxic species in Alzheimer's Disease (AD). Currently, little is known about intracellular Aβ in human brains mainly due to a lack of a technology to access the proteomic cell content. Here, we developed a microfluidic assay for in situ mass spectrometry (MS) detection of immunocaptured Aβ from microdissected human brain cells using our previously established MI crofluidic platform in tandem with MA LDI‐TOF MS (MIMAS). Moreover, Aβ monomers (Aβ‐M) and oligomers (Aβ‐O) were characterized extensively in vitro with multiple analytical techniques in preparation for the MIMAS assay from brain sections. Methods: To load cells directly on‐chip, the MIMAS platform was coupled with laser capture microdissection (LCM). After all sample preparation steps on‐chip, the elastomer platform is peeled‐off from the conductive substrate, which serves as the target in the MS analysis. We employed antibody 6E10 for the affinity capture. Aβ‐M and Aβ‐O were prepared and analyzed by gel electrophoresis, MALDI‐MS, and atomic force microscopy (AFM). Photo‐induced cross‐linking of unmodified proteins (PICUP) was used to cross‐link Aβ. Results: The LCM‐MIMAS coupling allowed for cell loading on‐chip with 70% efficiency. We further implemented Aβ immunocapture on‐chip showing the functioning principle of the assay in the microfluidic format. Gel characterization of native Aβ did not resolve Aβ‐O, while the cross‐linked Aβ‐O species obtained with the PICUP technique were successfully observed. MALDI‐MS spectra of native Aβ‐O showed a range of different oligomeric species, up to 8‐mers for Aβ40 and 12‐mers for Aβ42, showing the capability to detect native Aβ‐O with cross‐linking. AFM imaging revealed oligomer heights of 1.38±1.03 nm for Aβ40 ‐O and 11.25±10.4 nm for Aβ42 ‐O. In agreement with MALDI, AFM showed larger oligomers for Aβ42 ‐O. Conclusions: The LCM‐MIMAS approach could overcome the current limitations of accessing protein cell content, allowing the study of Aβ from brain cells. The Aβ characterization will facilitate the optimization of the assay. We plan to study soluble Aβ species from specific cell subpopulations in post‐mortem brain tissue from the frontal cortex and hippocampus regions. The identification of AD‐related Aβ species in brain cells could provide valuable insights into the disease.